ADAPTING LEARNING MATERIALS TO FACILITATE A BALANCED ACQUISITION OF LANGUAGE SKILLS, VALUES, AND 21ST CENTURY SKILLS - Priyana, Joko (Diksi, 2019)
(Title: Adapting Learning Materials To Facilitate A Balanced Acquisition Of Language Skills, Values, And 21st Century Skills). English language teaching in the Indonesian schools aims to develop the students' four language skills (listening, speaking, reading, and writing) in the target language and promote the acquisition of values and 21st century skills (critical thinking, creativity, collaboration, and communication). The learning materials published by the government and publishers available in the market generally focus on the development of the student's language skills and values. Hence, the learning materials should be adapted before being used so that the learning materials do not only promote the acquisition of language skills and values, but also 21st century skills. There are a number of alternatives of that teachers can use in adapting the learning materials to promote the acquisition of 21st century skills. Some of the alternatives include adapting the task input, activity/procedure, setting, and learner role and adding tasks to units and units to the textbook. Keywords: learning material, language skill, values and 21st century skill